Regional Cerebral Blood Flow Abnormalities in Neurosyphilis: A Pilot SPECT Study - Im, Jooyeon J.; Jeong, Hyeonseok; Kim, Young Do; Jang, Kyung-Sool; Song, In-Uk; Chung, Yong-An (Frontiers in Neurology, 2021)
Objective: Clinical and radiological findings on neurosyphilis are fairly nonspecific and there is a paucity of functional neuroimaging studies on neurosyphilis other than case reports and case series. The purpose of this study was to investigate brain perfusion abnormalities in patients with neurosyphilis. Methods: Four HIV-negative neurosyphilis patients and 4 healthy controls underwent clinical evaluation, brain technetium-99m ethyl cysteinate dimer (99mTc-ECD) single-photon emission computed tomography (SPECT) imaging, and neuropsychological assessments which included the Mini-Mental State Examination (MMSE), Clinical Dementia Rating (CDR), Clinical Dementia Rating – Sum of Boxes (CDR-SOB), and Global Deterioration Scale (GDS). Voxel-wise differences in regional cerebral blood flow were compared between the two groups. Results: Neuropsychological test results indicated cognitive impairment in all patients. SPECT analysis revealed multifocal hypoperfusion predominantly in the frontal, insular, and posterior cingulate regions in neurosyphilis patients compared with healthy controls (family-wise error corrected p < 0.05). Conclusions: Together with previous findings, our results suggest that the hypoperfusion in the frontal, insular, and posterior cingulate regions may reflect cognitive impairments observed in neurosyphilis patients. Further studies with larger samples are needed to confirm our findings.